Smartphone assisted legal writing / Zeti Zuryani Mohd Zakuan and Rizauddin Saian - Mohd Zakuan, Zeti Zuryani; Saian, Rizauddin (Research Management Institute (RMI), 2017)
In Universiti Teknologi MARA, certain courses require students to take up law papers as one of the requirements to complete the course. Example of courses are Bachelor in Business Administration and Bachelor of Accountancy. These non-law students may not have difficulties when learning law but may find difficulties when trying to answer law questions as students are expected to answer exam question in form of an essay. Legal writing starts when students are required to answer law questions. Answering law questions is a huge problem to non-law students as they do not know where to start and what to write. For them, writing is perceived as a daunting task in law classes. To improve the writing process of answering law questions students are required to know the format of answering the questions. A study is carried out in order to find a new way to help non-law students who undertake law papers to answer law questions properly. The study developed a smartphone application that is able to guide the students throughout the writing process. It is called SALeW (Smartphone Assisted Legal Writing). It is timely for universities in Malaysia to venture into mobile learning as the interest and innovation of using mobile technologies has increase among students in Malaysia. SALeW is useful to the non-law students as it will guide the students as to the steps required in answering law questions. Lecturer needs to show the students what are required in the answer and later the students can practice writing on their own assisted by SALeW. SALeW can be used by having the students to install the application in their smartphones. The students then can use SALeW anywhere and everywhere to practise answering law questions as it will guide the students as to the steps required. By having SALeW, it will promote independent study which is in line with the 2015-2025 Malaysian Education Blueprint – Higher Education (PPPM-PT) which aims inter alia to produce holistic valuable graduates. Independent study is important to inculcate values among students which later can be reinforced and incorporated in the working environment upon graduation. Furthermore, this study also illustrates the support for blended learning program which is implemented in Universiti Teknologi MARA.